Kết quả xạ trị ngoài ung thư cổ tử cung - Ái, Nguyễn Thanh; Hiệp, Phạm Như; Cầu, Tôn Thất; Tùng, Nguyễn Đình; Tường, Phạm Nguyên; Dũng, Nguyễn Việt; Duy, Phan Cảnh; Châu, Cao Khả; Thọ , Võ Thế; Phúc, Nguyễn Văn; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.